Electromyographic analysis of superior belly of the omohyoid muscle and anterior belly of the digastric muscle in mandibular movements - Castro, H. A L; Resende, Luiz Antonio de Lima [UNESP]; Bérzin, F.; König, B. (My University, 1998)
The superior belly of the omohyoid muscle and the anterior belly of the digastric muscle, were studied electromyographically in 20 young volunteers. For each muscle, 1 pair of monopolar electrodes was employed. One was a surface electrode and the other a needle electrode, which was inserted in the belly of the muscle. The surface electrode was placed 1 cm apart from the needle electrode. The most marked action of both muscles was on the movement of lowering the mandible. They also act in those movements for the performance of which they have associated a component of lowering the jaw, propulsion, laterality to the right and the left and retrusion. They are not active in the resting position and during jaw movements of elevation, extrusion and protrusion. Both muscles are active most of the time, simultaneously, but it is not possible to demonstrate that there is a synchronism between their actions.
Keywords: electromyogram; face muscle; functional assessment; human; human experiment; jaw movement; neck muscle; normal human; Adult; Electromyography; Facial Muscles; Humans; Movement; Temporomandibular Joint